Waiver of Rights for Parties Objecting to Compensation in Land Acquisition for Public Interest - Gandhi, Afnan Karenina; Handayani, Sri Wahyu (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The transfer of land rights held by individuals to the state as the result of land acquisition for development in the public interest often gives problems in its implementation. One of those is the issue of the amount and form of compensation for the entitled parties. Specifically, this study discusses the procedure for submitting objections by the people communities and affected agencies as parties entitled to receive compensation due to land acquisition and questions the guarantee of justice and the realization of legal certainty in land acquisition’s implementation. This study uses a normative juridical method. Based on the research, it can be concluded that in the event of an objection regarding the amount and form of compensation, the entitled party can file an objection lawsuit with the district court and file a cassation appeal to the Supreme Court against the district court’s decision. Then, if the entitled party rejects the compensation after a cash payment offer has been made, the agency requiring the land can deposit the compensation money with the district court as consignment